Rethinking urban transformation : exploring possible construction and adaptive use of grey space under flyover / Siti Nur Aqilah Amanina Mohd Kassim and Md Azree Othuman Mydin - Mohd Kassim, Siti Nur Aqilah Amanina; Othuman Mydin, Md Azree (2019)
In recent years, there has been a growth in the population and migration of people from rural areas to urban settings. This phenomenon serves as a contributing factor to the increase number of flyovers. Since the number of flyovers has been increasing nowadays, the idea of utilizing spaces under flyovers has become a moot point. The increase number of flyovers also resulted in many leftover spaces available under flyover. These unplanned spaces, if utilized properly, offer an abundance of opportunities. Hence, this study focuses on exploring possible construction and adaptive use of “grey space” under flyover. The case study will be in three main cities which is Penang, Kuala Lumpur and Johor Bahru. This research will be conducted through a combination of site observations, interview and questionnaire surveys. The main objective of this research is to propose three suitable designs for adaptive use of “grey space” under flyover that comply with rules and regulations. As for the conclusion, the size and the location of flyover will determine what can be developed. Hence, without performing any large construction, we will be able to utilize the leftover space under flyover.